PROSEDUR DAN SYARAT POLIGAMI DI INDONESIA PERSPEKTIF MAQASHID SYARIAH - Fahmi, Muhammad Nurul; Muhammad Yassir; Zulfantri, Abdi (Sekolah Tinggi Dirasat Islamiyah Imam Syafi'i Jember, 2024)
Basically, polygamy in Islam is permissible. In fact, according to some scholars, the original law for marriage is polygamy, except for those who are afraid of not being fair, then they are permitted to marry one woman. However, some people in Indonesia have different views on polygamy, some consider it normal and some consider it inappropriate for someone who is good and has authority in society. The government neither agrees nor absolutely rejects people's views on polygamy, but they provide difficult conditions for anyone who wants to practice polygamy. If one pays attention to these conditions it is difficult to fulfill, making it almost impossible for a husband to legally practice polygamy according to the law. One of the conditions that is very difficult for a husband who wants to be legally polygamous is to obtain written permission from his wife. In fact, in Islamic law, a husband who wants to practice polygamy is not required to ask permission from his wife. On the other hand, the presence of Islamic sharia actually has a specific purpose. These goals have been compiled by the scholars with the term maqashid sharia. The principles of maqashid sharia are reflected in various matters in Islamic law, including the law on monogamous and polygamous marriages. With the difficulty of procedures and requirements for polygamy in Indonesia, it is feared that it will become an obstacle to achieving maqashid sharia through this polygamy sharia. The researchers are interested in conducting deeper research related to the suitability of polygamy procedures and requirements in Indonesia with the principles of maqashid sharia.